p50-associated Cyclooxygenase-2 Extragenic RNA (PACER) and Long Non-coding RNA 13 (LNC13) as potential biomarkers for monitoring tuberculosis treatment - Kameni, Charleine; Mezajou, Cybelle Fodieu; Ngongang, Natacha Njike; Ngum, Jubilate Afuoti; Simo, Ulrich Stephane Fotso; Tatang, Fabrice Junior; Nguengo, Sarah Ngate; Nouthio, Annick Prisca Chakam; Pajiep, Michelle Alma Wandji; Toumeni, Michelle Hako; Madjoumo, Epiphanie Sorelle Takou; Tchinda, Maxwell Fofou; et al. (Frontiers in Tropical Diseases, 2022)
Gaps in early and accurate diagnosis, effective drug control, and treatment monitoring are hindering the global eradication effort of tuberculosis. This infectious disease has become the deadliest worldwide before the outbreak of Covid-19. The search for new molecular biomarkers of tuberculosis will help to reverse this trend. Long non-coding RNAs (lncRNAs) have emerged as important regulators of the host immune response to infection, hence their link with the etiology and diagnosis of tuberculosis has attracted some attention from the research community. However, very little is known about their potential for the monitoring of tuberculosis treatment. This study aimed at assessing the potential of two lncRNAs: p50-associated Cyclooxygenase-2 Extragenic RNA (PACER) and Long Non-coding RNA 13 (LNC13) in the monitoring of tuberculosis treatment. This was a cross-sectional study carried out in Douala, Cameroon from December 2020 to August 2021. A quantitative real-time polymerase chain reaction followed by Cq analysis using the Livak method were performed to measure the relative expression levels of PACER and LNC13 in whole blood of healthy controls, patients with active pulmonary tuberculosis at the initiation of treatment, after two, five, and six months into treatment. Receiver Operating Characteristic curves analysis was used to assess the ability of targeted lncRNAs to discriminate among those groups. The study showed that the lncRNAs PACER and LNC13 were significantly upregulated in patients with active pulmonary tuberculosis at the initiation of treatment than in healthy controls. The expression levels of the two lncRNAs were significantly downregulated in patients during the treatment as compared to the active pulmonary tuberculosis patients. However, the expression levels of the lncRNAs PACER and LNC13 in whole blood of patients after six months of treatment were similar to those in healthy controls. Similarly, lncRNAs PACER and LNC13 showed very good performance in distinguishing between active tuberculosis patients and healthy controls as well as in differentiating between newly diagnosed active tuberculosis patients and those under treatment. Interestingly, those lncRNAs could not discriminate healthy controls from patients after six months of treatment. The lncRNAs PACER and LNC13 are therefore potential biomarkers for the monitoring of tuberculosis treatment.